2020
DOI: 10.1371/journal.pone.0237567
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic green synthesis of MgO nanoparticles using Saussurea costus biomasses for a comprehensive detection of their antimicrobial, cytotoxicity against MCF-7 breast cancer cells and photocatalysis potentials

Abstract: Distinct morphological MgO nanoparticles (MgONPs) were synthesized using biomasses of Saussurea costus roots. The biomass of two varieties of Saussurea costus (Qustal hindi and Qustal bahri) were used in the green synthesis of MgONPs. The physical and chemical features of nanoparticles were confirmed by spectroscopic and microscopic techniques. The surface morphology of the obtained nanoparticles was detected at different magnifications by SEM and TEM microscopy and the size of nanoparticles were found to be 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 62 publications
4
62
0
Order By: Relevance
“…Best of our knowledge, Saussurea lappa plant extract used for the synthesis of the oxides of the Silver [ 66 ], Magnesium [ 67 ], and Selenium [ 68 ] but no literature available on a synthesis of ZnO-NPs. In the light of the above, herein reporting the preparation of ZnO nanoparticles from roots (rhizome) of Saussurea lappa plant methanol extract and its anti-bacterial, anti-fungal activities and cytotoxicity effect of ZnO nanoparticles against Chinese Hamster Ovary (CHO) cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Best of our knowledge, Saussurea lappa plant extract used for the synthesis of the oxides of the Silver [ 66 ], Magnesium [ 67 ], and Selenium [ 68 ] but no literature available on a synthesis of ZnO-NPs. In the light of the above, herein reporting the preparation of ZnO nanoparticles from roots (rhizome) of Saussurea lappa plant methanol extract and its anti-bacterial, anti-fungal activities and cytotoxicity effect of ZnO nanoparticles against Chinese Hamster Ovary (CHO) cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory concentrations (IC 50 ) calculated for AgNPs and polymeric bionanocomposite were 220.35 μg mL −1 and 135 μg mL −1 , respectively. The results illustrated the polymeric bionanocomposite induced more cell death than AgNPs due to the presence of magnesium oxide ions which are reported as a cytotoxic agent towards many cancer cell lines including MCF-7, HT 29, Hep2 cells ( Amina et al, 2020 , Saravanakumar and Wang, 2019 ). Furthermore, many studies have shown that the silver-doped nanoparticles can easily penetrate the cell membrane and induce the free radicals, production of ROS and trigger the damage of the nucleus ( Jayapriya et al, 2020 ).…”
Section: Resultsmentioning
confidence: 91%
“…Researches for the biological effects of phytocomplex could contribute to find out the bioactive single molecule studied [6,7]. Indeed, as previously reported, costunolidecontaining phytocomplexes showed cytotoxic properties in various cancer cell lines [8][9][10]. Costunolide is a sesquiterpene lactone first obtained from the costus (Saussurea lappa Clarke) root [11] and subsequently isolated from several species of plants, including Aucklandia lappa Decne [12], Laurus nobilis [13], Magnolia grandiflora [14], and Michelia floribunda [15].…”
Section: Introductionmentioning
confidence: 92%